Developing an in-depth understanding of acute pain assessment and management in the prehospital setting in the Western Cape, South Africa, the factors influencing practice and what improvement measures could advance prehospital acute pain management - Lourens, Andrit (Division of Emergency Medicine, 2021)
Introduction: Acute pain is a common reason for seeking emergency care in the prehospital and emergency centre settings where pain prevalence ranges widely. Pain is a significant global health problem which often goes unnoticed and is undermanaged. To this end, a project consisting of a series of research studies aimed to develop an understanding of acute prehospital pain assessment and management in South Africa was conducted to identify how best to improve this field. Methods: The project consisted of four distinct objectives to be investigated as separate but interconnected studies. The first objective was answered through a secondary research methodology (scoping review) to identify and map the body of evidence on acute prehospital pain assessment and management in Africa. The remaining three objectives were answered using primary research methods in studies conducted in the Western Cape, South Africa. Two observational studies, (i) a cross-sectional online survey and (ii) a retrospective review, respectively, aimed to describe (i) the knowledge, attitudes and practices regarding prehospital acute pain assessment and management among emergency care providers and (ii) current prehospital acute pain assessment and management practices in high acuity trauma patients. The final study employed qualitative research methods using focus groups and content analysis to explore and describe emergency care providers' perspectives of acute pain assessment and management as well as perceived barriers and facilitators to pain management. Main results: In the scoping review, six publications on acute pain research in the African prehospital setting were identified, indicative of the paucity and immaturity of this research area. In the cross-sectional online survey, suboptimal levels of knowledge and attitudes regarding pain (58.01%) were found among emergency care providers, with gaps in all aspects of pain knowledge and attitudes of distrust in self-reported pain identified. The retrospective review recorded pain scores were documented in only 18.1% of the high acuity trauma patients reviewed, while moderate-to-severe pain (78.6%) was prevalent among those who had a pain score documented. Less than 3% of all trauma patients, and less than 8% of those with moderate-to-severe pain received analgesic medication, thus, suggesting less than ideal prehospital pain assessment and management practices. In the final qualitative study, six focus groups and one interview were conducted among 25 emergency care providers. Through content analysis five themes, namely: assessing pain is difficult in this setting; many factors affect clinical reasoning some unique to this (hostile) setting; basic and intermediate life support practitioners' reality of prehospital pain care; the emergency centre does not understand what we do, how we work, what it is like; and how can we do better; emerged from the data. Conclusion: Africa has a scarcity of prehospital pain research with current evidence mainly from South Africa while knowledge of prehospital pain assessment and management in the Western Cape, South Africa proved to be a significant gap. This gap appears to be underpinned by limited educational focus, lack of pain prioritisation in emergency medical services (EMS) organisations, lack of clear evidence-based prehospital pain clinical practice guidelines, and emergency care providers' indifference towards prehospital pain care. A joint approach from EMS organisations and educational institutions, coupled with clinical practice guideline development, as well as interdisciplinary collaboration between prehospital emergency care and emergency medicine, are required. Further research must focus on developing the body of African prehospital pain knowledge to inform clinical practice and advance quality prehospital pain care.